Evaluating impact of a multi-dimensional education programme on perceived performance of primary care professionals in diabetes care. Issue 6 (19th March 2015) - Parekh, Sanjoti; Bush, Robert; Cook, Susan; Grant, Phillipa
Abstract : Aim: The purpose of this study is to evaluate an educational programme, 'Diabetes Connect: Connecting Professions', which was developed to enhance communication across primary care networks, to support best practice in clinical interventions and progress multidisciplinary team work to benefit patients in diabetes care. Methods: A total of 26 workshops were successfully delivered for 309 primary care professionals across the state of Queensland in Australia from November 2011. It consists of two separate, but complementary training elements: a series of online clinical education training modules and state-wide interprofessional learning workshops developed to enhance professional competencies. The evaluation design included completion of online surveys by the participants at two time points: first upon registering for the online modules or workshops; second, one week after attending a workshop. The survey included questions to evaluate the change in role performance measures. Findings: Overall, significant increases in participants' current knowledge, perceived ability to adopt this knowledge at work and willingness to change professional behaviour in the short term were observed. Conclusion: The study suggests that for maximum benefit both, workshop and online training, should be combined and made available widely. Future programmes should use a randomised trial design to test the delivery model.